Analysis of Inheriting Folk Culture under the Background of News Media - Liu, Xiaoxiao; Wenxiao Shen (CV. AFDIFAL MAJU BERKAH, 2025)
This research aims to explore practical strategies for news media to inherit folk culture. The news media has presented a new situation in inheriting folk culture, breaking through traditional barriers, expanding communication space and channels, providing new opportunities for cultural integration and collision, and promoting the prosperity of the cultural industry. Through the analysis of the specific performance of news media in the dissemination of folk culture, as well as the practical strategies of giving play to the role of media gatekeepers, updating Internet thinking, establishing the awareness of content as king, and improving the awareness of folk culture, etc. The results showed that news media activated young audiences through precise dissemination of big data, cross media storytelling, and digital technology, increased attention to folk culture, and led to a 217% increase in related e-commerce search volume. Strategically integrating content innovation and technological empowerment, balancing commercial and cultural protection, promoting cultural industrialization, and building a